An Autologous Muscle Tissue Expansion Approach for the Treatment of Volumetric Muscle Loss - Ward, Catherine L. (Biores Open Access, 2015)
Volumetric muscle loss (VML) is a hallmark of orthopedic trauma with no current standard of care. As a potential therapy for some VML indications, autologous minced muscle grafts (1 mm(3) pieces of muscle) are effective in promoting remarkable de novo fiber regeneration. But they require ample donor muscle tissue and therefore may be limited in their application for large clinical VML. Here, we tested the hypothesis that autologous minced grafts may be volume expanded in a collagen hydrogel, allowing for the use of lesser autologous muscle while maintaining regenerative and functional efficacy. The results of the study indicate that 50% (but not 75%) less minced graft tissue suspended in a collagen hydrogel promoted a functional improvement similar to that of a 100% minced graft repair. However, approximately half of the number of fibers regenerated de novo with 50% graft repair. Moreover, the fibers that regenerated had a smaller cross-sectional area. These findings support the concept of using autologous minced grafts for the regeneration of muscle tissue after VML, but indicate the need to identify optimal carrier materials for expansion.